2014
DOI: 10.3390/ma7107010
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of 3C-Inclusion Formation during Growth of 4H-SiC Si-Face Homoepitaxial Layers with a 1° Off-Angle

Abstract: We grew epitaxial layers on 4H-silicon carbide (SiC) Si-face substrates with a 1° off-angle. The suppression of 3C-inclusion formation during growth at a high C/Si ratio was investigated, because a growth technique with a high C/Si ratio is needed to decrease residual nitrogen incorporation. 3C inclusions were generated both at the interface between the substrate and epitaxial layer, and during epitaxial growth. 3C-SiC nucleation is proposed to trigger the formation of 3C inclusions. We suppressed 3C-inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…shows an SEM image of the same sample. A set of 9 nm steps with 300 nm spacing were observed, indicating the occurrence of step bunching, similar to what has been reported for CVD growth at higher temperatures [10]. A separate test revealed that the hydrogen etch causes the step bunching, while the steps are preserved during the subsequent growth.…”
Section: Epitaxial Growth Descriptionsupporting
confidence: 84%
“…shows an SEM image of the same sample. A set of 9 nm steps with 300 nm spacing were observed, indicating the occurrence of step bunching, similar to what has been reported for CVD growth at higher temperatures [10]. A separate test revealed that the hydrogen etch causes the step bunching, while the steps are preserved during the subsequent growth.…”
Section: Epitaxial Growth Descriptionsupporting
confidence: 84%
“…As reported for Si-face epitaxial growth with a low off-angle of less than 1°, the 3C inclusion density increases as the C/Si ratio increases because 3C-SiC nucleation occurs due to the short diffusion length of adatoms and the wide terrace width caused by step bunching generation. 11,21,22) Compared with the reported Si-face epitaxial growth, the 3C-inclusion density on the C-face did not increase as the C/Si ratio increased. With C-face epitaxial growth, we consider that 3C inclusions, which were attributed to 3C-SiC nucleation occurred by the wide terrace width, were not generated since the terrace width was not increased by the suppression of step bunching because of its lower surface energy compared with a Si-face.…”
Section: Discussion Of 3c Inclusion-density Reductionmentioning
confidence: 75%
“…[1][2][3][4] In the case of epitaxially grown substrates, offorientation is employed to prevent the poly-type inclusion phenomenon during epitaxial growth for the low-doped layer. 5,6) However, the off-orientation of 4H-SiC causes serious surface scattering for electrons at the interface between 4H-SiC and the gate insulator in the lateral MOSFETs. Although several studies to suppress poly-type inclusion and obtain a smooth surface during on-axis or on-axis-like (0.1-0.4°) epitaxial growth of SiC have been reported, [6][7][8][9][10] the uniform formation of 4H-SiC on epitaxial layers with reduced off-orientation still remains a problem.…”
Section: Introductionmentioning
confidence: 99%